Avaliação fisiológica multigeracional com exposição contínua a concentrações-traço de resíduos do organoclorado DDT - Silva, Fernanda Coleraus (2024)
For decades, the pesticide DDT (Dichlorodiphenyltrichloroethane) was extensively used for agricultural pest control and disease vector management. However, its use led to persistent environmental contamination with its degradation products, the residues DDD (Dichlorodiphenyldichloroethane) and DDE (Dichlorodiphenyldichloroethylene). Despite its commercial ban in Brazil since 2009, the environmental persistence of DDT ensures that populations remain continuously exposed to trace concentrations of its residues. Studies have linked exposure to DDT residues at different life stages to adverse health outcomes, including potential cytotoxic effects, metabolic damage, and reproductive impairments over prolonged exposure periods. Thus, the aim of this study was to investigate the potential physiological alterations induced by continuous exposure to trace concentrations of DDT residues across two generations of Wistar rats. To this end, water containing trace concentrations of isolated and mixed DDT residues was provided to different generations of rats (parental generation, F1, and F2) throughout their entire lifespan. Physiological and reproductive aspects were evaluated at various ages across the two generations. The results were divided into two articles. The first article, titled "Multigenerational Exposure to Trace Concentrations of DDT Residues in Wistar Rats: Effects on Biometric Development and Biochemical Parameters," demonstrated that continuous exposure to trace concentrations of DDT metabolites and their accumulation in tissues were key determinants of alterations in brain, liver, kidney, and adipose tissues. Tissue evaluations using a hypothetical model revealed that the DDD/DDE synergism and sex-specific factors were associated with the observed effects in all analyzed tissues. Daily doses 10 times lower than the LOAEL for p,p’- DDD and 3000 times lower than the LOAEL for p,p’-DDE were sufficient to cause potential tissue disruptions at the onset of puberty (PND35). These exposures also contributed to changes in adipocyte mass and biometric development in adulthood (PND105), particularly in females. The second article, titled "Multigenerational Exposure to DDT Residues: What Happens to the Male Reproductive System?" highlighted increased activities of antioxidant enzymes (SOD, CAT, and GPx) associated with reduced sperm motility in adult males (PND35) of the first generation (F1). Subsequently, a reduction in sperm concentration was observed, linked to the interference of DDT residues with the actions of sex hormones, testosterone, and estradiol, in adult males of the second generation (F2). These findings underscore that even minimal concentrations of DDT residues present in the environment can pose significant harm to exposed organisms, emphasizing the urgent need to develop effective public policies for diagnosis and monitoring to prevent and mitigate these impacts.